Decostruire l'archivio come forma di potere: Conversazione con Arkadi Zaides (Connessioni remote. Artivismo_Teatro_Tecnologia, 2023)
The proposal is a reflection on the research of multidisciplinary artist Arkadi Zaides in the form of a conversation. The artist, recognized for the personal methodology he calls "Documentary Choreography", investigates the relationship between scene, technology and power. Many of his works make tangible the geopolitical issues underlying some repositories of information. Such is the case with B'Tselem at the heart of the performance Archive (2015), to the list of deaths compiled by UNITED for Intercultural Action that prompts Necropolis (2020), to the movements of the Chernobyl radioactive cloud in the latest work The Cloud (2023). On closer inspection, these works simultaneously lay bare the pressing political issues "housed" in these databases and the data visualization systems themselves. It is "not just" about embodying the archive, but deconstructing the device-archive as a power structure.